Analysis of Women's Involvement in Marine Mining: Motivation, Challenges, and Perceptions of the Local Community of Belo Laut Village Mentok District West Bangka Regency - Rangga Juanda; Naswa Okta; Suci Espiana; Aditya Putra; Ririn Septia (MUWAZAH : jurnal kajian gender, 2025)
This study analyzes the involvement of women in the marine mining sector in Belo Laut Village, Mentok District, West Bangka Regency. Mining activities are indetik with masculine activities that must have physical strength, but women in Belo Laut Village play an important role in going through mining activities commonly called "Ngereman", namely bartering basic necessities with tin mining products. The data was then reduced, analyzed and interpreted with the aim of exploring the motivations, challenges and perceptions of local communities in the involvement of women in the mining sector. The results of this study show that the factor of women's involvement in the mining sector is an economic factor so that women carry out "Ngereman" activities. The challenges faced are such as a poor environment, the presence of substances that harm the body to the existence of forms of sexual harassment, both verbal and non-verbal. This mining activity has given rise to a very diverse perception of women's involvement, with some considering it a reasonable economic adaptation and part of local traditions. The results of this study are expected to provide recommendations to both the local and central governments to recognize the existence of women in informal mining activities, such as ngereman, and provide special protection regulations related to the safety, health, and rights of women in this sector. In addition, a policy of limited legal recognition of "ngereman" activities as part of the informal economy that supports poor families, accompanied by supervision and social protection mechanisms, is needed.